2013
DOI: 10.1111/hsc.12070
|View full text |Cite
|
Sign up to set email alerts
|

Projecting social support needs of informal caregivers in Malaysia

Abstract: This article presents the findings of a self-report study of the consequences of being an informal caregiver in Malaysia. The aim of this exploratory study was to examine Malaysian efforts in assisting informal caregivers, based on an analysis of the issues and concerns raised by the caregivers themselves. Data were obtained from a cross-sectional survey of informal caregivers in 2009. This sample comprised parents, spouses and/or adult siblings, and adult children, caring for their children, spouses or siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Although the Saudi health system is comprehensive and free to all citizens , more than half of the current participants were not served well; this may result from an absence of LTC options satisfying the variety of nonmedical health needs . Additionally, recent studies have found that inadequate income was of a great concern among informal caregivers. The incomes in this study were not very high, although most of the participants had a job.…”
Section: Discussionmentioning
confidence: 96%
“…Although the Saudi health system is comprehensive and free to all citizens , more than half of the current participants were not served well; this may result from an absence of LTC options satisfying the variety of nonmedical health needs . Additionally, recent studies have found that inadequate income was of a great concern among informal caregivers. The incomes in this study were not very high, although most of the participants had a job.…”
Section: Discussionmentioning
confidence: 96%
“…Although this result contrasts with some earlier research (cf. Abu Bakar, Weatherley, Omar, Abdullah, & Aun, 2014), it simultaneously highlights the uniqueness of each individual caregiver's situation. In place of emotional support, focus group participants emphasized that they lacked more tangible forms of support, and especially the sharing of caregiver responsibilities to help alleviate some of the stress associated with balancing their caregiving and other responsibilities.…”
Section: Meeting the Needs Of Informal Caregiversmentioning
confidence: 99%
“…When a stroke survivor develops long-term disability, the role of caregivers is of utmost importance in the rehabilitation and nursing care of the patient. The majority of stroke caregivers in Malaysia are informal caregivers, comprising family members of the patients [1][2]. Very few Malaysian families can afford paid caregivers, whether trained or untrained [1].…”
mentioning
confidence: 99%
“…Informal caregivers have been found to have a higher prevalence of depression, as well as the negative effects of their physical, psychological, and social health [6]. In Malaysia, stroke caregivers also face unmet needs in terms of information regarding problem-solving and medical-related knowledge, financial, and social support [2]. The burden faced by caregivers has been associated with various negative impact toward patients' well-being, such as increased poststroke depression, cognitive decline, physical disability, and general quality of life [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation